EXTH-101. MECHANISTIC INSIGHTS INTO CYTOTOXIC EFFECTS OF LETROZOLE AGAINST GLIOBLASTOMA CELLS. (14th November 2022) - Karve, Aniruddha; Desai, Janki; Dave, Nimita; Phoenix, Timothy; Gudelsky, Gary; Plas, David; Dasgupta, Biplab; Wise-Draper, Trisha; Desai, Pankaj
Abstract: PURPOSE: Despite significant advances in multimodal approaches for the treatment of glioblastoma (GBM), the outcome for the patients remains dismal. Previous research from our lab has shown that aromatase (CYP19A1), an enzyme that catalyzes in situ production of estrogens, is markedly elevated in GBM tissues. Additionally, letrozole (LTZ), an aromatase inhibitor with extensive record of efficacious use in breast cancer, exhibited significant activity against GBM in preclinical studies. The purpose of this study was to investigate the mechanism(s) of LTZ activity in GBM. METHODS: Patient-derived GBM cells with varying aromatase expression and other genotypic/phenotypic characteristics were employed including aromatase expressing G43, G75, G76, BT-142-gfp-luc and aromatase-null G80 cells. The effects of LTZ on cell viability, neurosphere growth, DNA damage (assessed by measuring phosphorylated histone product ỴH2A.X using flow cytometry) and induction of apoptosis (caspase3/7 activity) were assessed. The effects of exogenous addition of estradiol (E2) was also examined. RESULTS: LTZ treatment (72 hours) caused a marked reduction in viability and growth of all GBM cells (IC50 ranging from 0.08 to 0.7 µM) except in G80 cells where LTZ had no effects. LTZ treatment also resulted in inhibition of E2 synthesis in a time and dose-dependent fashion. Furthermore, in aromatase expressing cells LTZ treatment induced apoptosis as measured by increase in Caspase-3/7 activity and triggered significant DNA double strand break as determined by ỴH2A.X formation. The addition of exogenous E2 (250 pg/ml) abrogated the effects of LTZ on cell viability, DNA damage and induction of apoptosis. CONCLUSIONS: Our study suggests that the cytotoxic effects of LTZ against GBM are mediated, at least partially, by the inhibition of aromatase activity which results in estrogen deprivation. These mechanistic insights are important to facilitate repurposing LTZ as a novel anti-GBM drug.